Television in Cameroon: Upshots from Monopoly to Fierce Competition - Ndode, Stephen N.; Ngange, Kingsley L. (Advances in Social Sciences Research Journal, 2025)
On Wednesday, March 19, 2025, the Top Management of Cameroon Radio Television (CRTV) – the State broadcaster and first television (then CTV) in Cameroon, invited us as panelists in a symposium to mark 40 years of television in Cameroon (March 1985 - March 2025). Our presentation highlighted that the TV landscape in Cameroon has burgeoned from Cameroon Television’s (CTV) monopoly in 1985 to 93 independent channels today. This shift has removed the power of monopoly from the hands of CTV (now CRTV), implying the infusion of diverse opinions and audience interactions with choicest channels and programs. That is not enough – the television industry in Cameroon faces stiff competition from 760 media in the country, in addition to the ever-present and intrusive foreign media with considerable audience followings. Though television and media pluralism and diversity in Cameroon have brought dynamism, existing gaps have widened in news and information production, dissemination, and consumption. The theory of media pluralism is used to reflect on the degree to which the media landscape of Cameroon; particularly television, has soared from monopoly to fierce competition, with varied inferences on viewership patterns and media effects